2005
DOI: 10.1167/iovs.04-1253
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Collagen Orientation and Distribution in Keratoconus Corneas

Abstract: The development of keratoconus involves a high degree of inter- and probably intralamellar displacement and slippage that leads to thinning of the central cornea and associated changes in corneal curvature. This slippage may be promoted by a loss of cohesive forces and mechanical failure in regions where lamellae bifurcate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
320
1
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 441 publications
(346 citation statements)
references
References 51 publications
10
320
1
15
Order By: Relevance
“…Despite the considerable variability known to exist between keratoconus corneas in terms of the extent of stromal collagen disruption, 14 X-ray scattering and scanning electron microscopy studies are in agreement that the severity of disruption decreases with distance from the cone apex. 13,14,18,19 In contrast to most keratoconus corneal buttons, the majority of the failed-graft tissue appeared normal in terms of collagen orientation and mass distribution, with regions of abnormality being limited to the inferior aspect of the peripheral cornea and coinciding in each case with the location of the original graft-host interface. The most marked abnormalities were observed in the grossly vascularised infero-nasal quadrant of the peripheral cornea, where the normal tangential alignment of collagen was replaced by radially orientated collagen and the lamellae appeared indistinct and disordered when viewed by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the considerable variability known to exist between keratoconus corneas in terms of the extent of stromal collagen disruption, 14 X-ray scattering and scanning electron microscopy studies are in agreement that the severity of disruption decreases with distance from the cone apex. 13,14,18,19 In contrast to most keratoconus corneal buttons, the majority of the failed-graft tissue appeared normal in terms of collagen orientation and mass distribution, with regions of abnormality being limited to the inferior aspect of the peripheral cornea and coinciding in each case with the location of the original graft-host interface. The most marked abnormalities were observed in the grossly vascularised infero-nasal quadrant of the peripheral cornea, where the normal tangential alignment of collagen was replaced by radially orientated collagen and the lamellae appeared indistinct and disordered when viewed by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were compared with our previously published work (using the same experimental protocol as here), which examined six normal corneas 12 and six keratoconus corneas. 13,14 Measurements of fibril diameter in the failed-graft corneal tissue were compared with those obtained from an 8.5-mm button excised from a normal post-mortem cornea stored for 23 days in culture medium and then de-swelled for 2 days in dextran (obtained from the Corneal Transplant Service Eye Bank, Bristol, UK). Our previously published results from five healthy corneas 15 were used to confirm the normal range of fibril diameters in the human cornea.…”
Section: Specimen Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes allow more contact between the collagen sheets and the proteoglycans, thus altering the stroma organization where alterations in interlamellar proteoglycans might contribute to slippage of the lamellae. 81 Meek et al, 82 using synchrotron X-ray scattering patterns, confirmed that a gross rearrangement of vertical and horizontal collagen lamellae occurs in keratoconus. Tissue degradation alone does not account for that systematic realignment of fibrils, and so the authors suggested that both slippage and remodeling have a role.…”
Section: Corneal Stroma Compositionmentioning
confidence: 92%
“…Structural abnormalities were occurred in the central part of Bowman's layer (BM) in the form of a sharp edge defects and interruption in the BM resulting from collagen bundle separation. 3 Computer-assisted videokeratography (corneal topography) was one of the recent methods of diagnosis of keratoconus which depends on screening for keratoconic corneal shape changes. It depends on Rabinowitz diag nostic indices for diagnosis of keratoconus.…”
Section: Introductionmentioning
confidence: 99%